Leishmania donovani visceral leishmaniasis diagnosed by metagenomics next-generation sequencing in an infant with acute lymphoblastic leukemia: a case report - Li Chang; Li Chang; Guanglu Che; Guanglu Che; Qiuxia Yang; Qiuxia Yang; Shuyu Lai; Shuyu Lai; Jie Teng; Jie Teng; Jiaxin Duan; Jiaxin Duan; et al. (Frontiers in Public Health, 2023)
BackgroundVisceral leishmaniasis (VL) is a neglected vector-borne tropical disease caused by Leishmania donovani (L. donovani) and Leishmania infantum (L. infantum). Due to the very small dimensions of the protozoa impounded within blood cells and reticuloendothelial structure, diagnosing VL remains challenging.Case presentationHerein, we reported a case of VL in a 17-month-old boy with acute lymphoblastic leukemia (ALL). The patient was admitted to West China Second University Hospital, Sichuan University, due to repeated fever after chemotherapy. After admission, chemotherapy-related bone marrow suppression and infection were suspected based on clinical symptoms and laboratory test results. However, there was no growth in the conventional peripheral blood culture, and the patient was unresponsive to routine antibiotics. Metagenomics next-generation sequencing (mNGS) of peripheral blood identified 196123 L. donovani reads, followed by Leishmania spp amastigotes using cytomorphology examination of the bone marrow specimen. The patient was given pentavalent antimonials as parasite-resistant therapy for 10 days. After the initial treatment, 356 L. donovani reads were still found in peripheral blood by mNGS. Subsequently, the anti-leishmanial drug amphotericin B was administrated as rescue therapy, and the patient was discharged after a clinical cure.ConclusionOur results indicated that leishmaniasis still exists in China. Unbiased mNGS provided a clinically actionable diagnosis of a specific infectious disease from an uncommon pathogen that eluded conventional testing.